2006
DOI: 10.1111/j.1532-5415.2006.00733.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an In‐Home Occupational and Physical Therapy Intervention on Reducing Mortality in Functionally Vulnerable Older People: Preliminary Findings

Abstract: An occupational and physical therapy intervention to ameliorate functional difficulties may reduce mortality risk in community-dwelling older people overall and benefit those most compromised. Instruction in control-oriented strategies may account for the intervention's protective effects on survivorship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
100
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(101 citation statements)
references
References 24 publications
1
100
0
Order By: Relevance
“…The mean age of all participants was 79 years, and 69% of the participants were women (supplementary materials/appendix 1). The methodological quality of included trials varied; seven trials (Hall et al 1992;Leveille et al 1998;Mann et al 1999;Dalby et al 2000;Rockwood et al 2000;Chin et al 2001;Phelan et al 2004;Holland et al 2005) were of low quality according to the criteria (van Tulder et al 2003), and seven trials were of high quality (Dalby et al 2000;Stuck et al 2000;van Haastregt et al 2000;Hebert et al 2001;Gill et al 2002Gill et al , 2004Gitlin et al 2006a;b;Markle-Reid et al 2006) ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean age of all participants was 79 years, and 69% of the participants were women (supplementary materials/appendix 1). The methodological quality of included trials varied; seven trials (Hall et al 1992;Leveille et al 1998;Mann et al 1999;Dalby et al 2000;Rockwood et al 2000;Chin et al 2001;Phelan et al 2004;Holland et al 2005) were of low quality according to the criteria (van Tulder et al 2003), and seven trials were of high quality (Dalby et al 2000;Stuck et al 2000;van Haastregt et al 2000;Hebert et al 2001;Gill et al 2002Gill et al , 2004Gitlin et al 2006a;b;Markle-Reid et al 2006) ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…It is unknown whether some of the intervention components were more effective than others, although it is likely that it was the multi-component approach, the sum of all components, that led to the positive outcome verified in a number of programmes. The view that the sum of the parts in an intervention programme is greater than the value of each separate part is supported by Gitlin et al (2006a;b). Others (Beswick et al 2008), with future research in mind, suggest that a qualitative approach to study different HPDP interventions may help us to gain a better understanding of the complexity of the interventions, and how the participants experience them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relevant to problem-focused coping, a recent review of empirical findings based on the life-span theory of control (Heckhausen et al, 2010) found that use of primary control strategies is universally preferred and beneficial across the life-span. For example, older adults with functional constraints who used primary control strategies had lower risk of mortality (Gitlin, Hauck, Winter, Dennis, & Schulz, 2006) and less difficulty with everyday activities (Gitlin, Winter, Dennis, Corcoran, Schinfeld, & Hauck, 2006). However, although use of primary control strategies remains relatively stable in young, middle-aged, and older adults, use of secondary control strategies increases across adulthood (Brandtstädter & Renner, 1990;Heckhausen, 1997;Wrosch, Bauer, & Scheier, 2005).…”
Section: Coping With Job Loss and Agementioning
confidence: 99%
“…Home-visit rehabilitation performed about once every 1-2 months has also been reported to reduce the risk of death 6) . However, in rural areas deficient in rehabilitation resources, home-visit rehabilitation is difficult to perform, and support for home-dwelling disabled persons has been generally inadequate.…”
Section: Introductionmentioning
confidence: 99%